2017
DOI: 10.1111/febs.14321
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of TGFBI‐null mouse corneas reveals only minor changes in matrix composition supportive of TGFBI knockdown as therapy against TGFBI‐linked corneal dystrophies

Abstract: TGFBIp is a constituent of the extracellular matrix in many human tissues including the cornea, where it is one of the most abundant proteins expressed. TGFBIp interacts with Type I, II, IV, VI, and XII collagens as well as several members of the integrin family, suggesting it plays an important role in maintaining structural integrity and possibly corneal transparency as well. Significantly, more than 60 point mutations within the TGFBI gene have been reported to result in aberrant TGFBIp folding and aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…We have previously shown that the major fraction of corneal mouse TGFBIp originated from the corneal epithelium (6). Furthermore, quantification showed abundant HtrA1 protein in the corneal proteome of the endothelial layer, including Descemet's membrane (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the major fraction of corneal mouse TGFBIp originated from the corneal epithelium (6). Furthermore, quantification showed abundant HtrA1 protein in the corneal proteome of the endothelial layer, including Descemet's membrane (1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TGFBIp binds covalently to type XII collagen via a reducible bond (5). Knocking out TGFBIp in mice showed little effect on corneal integrity and mouse behavior in general (6). TGFBIp is involved in the pathophysiology of the amyloid corneal disease lattice corneal dystrophy (LCD) 3 and amorphous granular corneal dystrophy (GCD).…”
Section: Introductionmentioning
confidence: 99%
“…which is supported by the lower molar percentage in our results compared to the human corneal proteome. [9] The disease mechanism of TGFBI-linked corneal dystrophies has in several studies been linked to altered stability and aberrant proteolytic processing of the disease-causing TGFBIp mutants. [4,8,10] We performed 2DE of the proteins in the right cornea of the different genotypes and subsequently immunoblotted against TGFBIp.…”
Section: Doi: 101002/prca201900072mentioning
confidence: 99%
“…This is due to the thermal and pH instability of the protein and to its high abundance in the cornea [ 85 ]; however, the condition might not help us to understand HsTgfbi function. A complete Tgfbi gene knockout in mice caused neither corneal abnormalities nor any other major defects [ 86 ], suggesting compensation by other ECM molecules. Although Pn knock-out mice showed that this locus is essential for normal osteogenesis and dental development [ 87 , 88 ], the two closely-related Pn and Tgfbi loci function identically in many ways [ 43 ].…”
Section: Biological Aspects Of Fas1 Domain Proteins Across the Trementioning
confidence: 99%